2020
DOI: 10.3390/foods9060772
|View full text |Cite
|
Sign up to set email alerts
|

Development of High-Moisture Meat Analogues with Hemp and Soy Protein Using Extrusion Cooking

Abstract: The interest in plant-based products is growing in Western countries, mostly due to health and environmental issues that arise from the consumption and production of animal-based food products. Many vegan products today are made from soy, but drawbacks include the challenges of cultivating soy in colder climates such as northern Europe. Therefore, the present study investigates whether industrial hemp (Cannabis sativa) could substitute soy in the production of high moisture meat analogues (HMMA). A twin screw … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(98 citation statements)
references
References 28 publications
4
92
0
2
Order By: Relevance
“…The stabilization of the aligned proteins is achieved through newly developed covalent bonds, either disulfide [ 30 , 31 , 32 , 33 , 34 , 35 ] or isopeptide bonds [ 29 , 36 ]. Later studies on HME adapted the theory of protein alignment and reported correlations between the changes in protein–protein interactions and the product structure [ 27 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…The stabilization of the aligned proteins is achieved through newly developed covalent bonds, either disulfide [ 30 , 31 , 32 , 33 , 34 , 35 ] or isopeptide bonds [ 29 , 36 ]. Later studies on HME adapted the theory of protein alignment and reported correlations between the changes in protein–protein interactions and the product structure [ 27 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…The value of WAI highly depends on the nature of the proteins. The WAI value of hemp protein concentrate was lower than that of soy protein isolates [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…At present, commercial protein sources such as soy, wheat gluten (WG), pea, mycoprotein, egg albumin, and milk protein are commonly used in meat analog formulations (Alexander et al., 2017a; de Boer et al., 2013; Gómez‐Luciano et al., 2019; Insights, 2016; Smetana et al., 2015). Some new protein sources, such as mung bean, peanut, fava bean, lupine, mucuna bean, zien, insect protein, hemp, algae, and seaweed, have also shown promising results in recent studies on meat analogs (Batista et al., 2012; Brishti et al., 2017; Bühler et al., 2020; Jones, 2016; Jongen & Meerdink, 2001; Joshi & Kumar, 2015; Malav et al., 2015; Manski et al., 2007b; Mattice & Marangoni, 2020; Omohimi et al., 2014; Osen et al., 2014; Palanisamy et al., 2019a; Palanisamy et al., 2019b; Smetana et al., 2018; Zahari et al., 2020; Zhang et al., 2018).…”
Section: Meat Analogs: Composition and Functionalitymentioning
confidence: 99%